Comparative analysis of spark ignition engine performance using RON 95 and RON 100 gasoline fuels / Hazim Sharudin ... [et al.] - Sharudin, Hazim; Che Mat, Sharzali; Azizuddin, Ahmad Hadri; Ab Hamid Pahmi, Muhammad Arif; Husin, Azmi; Ismail, Noor Iswadi; Mahamad Basri, Mahamad Hisyam (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
Most of the vehicles used by Malaysians have engines that only require petrol RON 95 to power the engine. However, many people claimed that utilising RON 100 instead of RON 95 for their vehicles will improve engine performance. Furthermore, many people speculate that using oil with a low octane level in an engine with low performance will affect the engine's performance. The goal of this research is to analyse and compare the engine performance and emissions on a spark ignition engine using gasoline RON 95 and RON 100. In this study, a single-cylinder four-stroke engine running with RON 95 and RON 100 has been tested on an engine dynamometer to evaluate the brake power, torque, specific fuel consumption, and exhaust emissions. The emissions from the engines have been determined using a gas emissions analyser. The outcomes of the experiment have been analysed based on engine torque, braking power, and exhaust emissions. Based on the analysis, torque, brake power, and emissions data obtained from the dynamometer engine, RON 100 has a higher and smoother performance than RON 95.